P426Delayed preconditioning-like protection against ischemia/reperfusion injury in the rat heart is associated with PPAR-alpha-mediated changes in metabolic genes and non-metabolic effects. (15th July 2014) - Ravingerova, T; Carnicka, S; Ledvenyiova, V; Barlaka, E; Galatou, E; Mandikova, P; Chytilova, A; Nemcekova, M; Kolar, F; Lazou, A
Abstract: Ischemia alters the balance between fatty acids (FA) and glucose utilization as the main ATP-producing pathways in the heart that may dramatically affect myocardial salvage upon ischemia/reperfusion (I/R). Genes encoding enzymes involved in metabolic processes are transcriptionally regulated by nuclear peroxisome proliferator-activated receptors (PPAR). PPAR-alpha isoform is mainly responsible for FA uptake/transport, beta-oxidation (FAO) and glucose transport/oxidation. During ischemia, it modulates substrates switch aimed at the adequate energy production to preserve cardiac function. However, the role of PPAR-mediated metabolic shifts in protective effects of preconditioning (PC) is relatively less investigated. We explored the effects of PPAR-alpha activation in a setting simulating a delayed PC in the rat heart and potential downstream genomic and non-genomic mechanisms involved. Animals were given PPAR-alpha agonist WY-14643 (WY, 1 mg/kg, i.p.) with or without PPAR-alpha antagonist MKK-886 (MKK), 24 hr prior to 30-min global ischemia/2-h reperfusion in Langendorff-perfused hearts. Sampling for measurement of the expression of PPAR-alpha and its target genes (MCAD, PDK-4, mCPT-1, GLUT-4) and gene of heme oxygenase-1 (HO-1) as a key antioxidative enzyme (real-time RT-PCR), as well as for the determination of levels and phosphorylation of survival proteins (Akt, eNOS) and markers of apoptosis (Bax, Bcl-2, caspase-3) was performed at baseline (prior to ischemia) and after I/R (WB analysis). Pretreatment with WY attenuated postischemic contractile dysfunction, reduced the severity of ventricular arrhythmias and limited the extent of lethal injury (infarct size). These cardioprotective effects were blunted by inhibitor of NO synthase L-NAME and reversed by MKK treatment indicating a PPAR-alpha-dependent response. Administration of WY remarkably enhanced the expression of PPAR-alpha and its target genes promoting FAO (MCAD, PDK-4 and mCPT-1) coupled with reduced expression of GLUT-4 responsible for glucose metabolism and with up-regulation of HO-1. In addition, enhanced Akt phosphorylation and eNOS expression, as well as changes in pro- and antiapoptotic markers (increased Bcl-2/Bax ratio, reduced caspase-3 cleavage) were observed in the WY-treated hearts. Up-regulation of PPAR-alpha target metabolic genes regulating FAO may underlie delayed protection in the rat heart. Potential non-metabolic effects of PPAR-alpha-mediated cardioprotection may involve activation of PI3K/Akt and its downstream targets, such as eNOS, and modulation of oxidative stress and apoptosis.